Media Coverage of Minority Issues in Jordan from the Viewpoint of the Elders (Sheikhs) and Minority Representatives: A Qualitative Study - Al-Souob, Hana Abdul-Rahman (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to investigate media coverage of minority issues in Jordan from the viewpoint of elders )sheikhs( and minority representatives. Methodology: This is a qualitative study which uses the inductive approach, conducting in-depth interviews with the study’s purposive sample which consists of 10 sheikhs and minority representatives of Al-Nawar (Bani Murra) and the Turkmen. Results: The study reveals that media coverage of minority issues in Jordan is limited and irregular, and that Jordanian TV and YouTube channels briefly present general topics about the minorities’ history, customs, and traditions, focusing on the their reliance on begging as a profession. Therefore, the study suggests that media in Jordan should meet the expectations of the minorities by focusing on more important topics like youth unemployment and the increasing levels of education especially among Al-Nawar. Conclusion: The study concludes that media in Jordan does not do justice to the minorities because it does not reflect their reality or tackle their central concerns. Hence, it does not have any positive effect on the lives of the minorities, which prevents them from maintaining a positive social image and achieving social acceptance.